If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + -1) = 3x(x + 1) Reorder the terms: 2(-1 + 5x) = 3x(x + 1) (-1 * 2 + 5x * 2) = 3x(x + 1) (-2 + 10x) = 3x(x + 1) Reorder the terms: -2 + 10x = 3x(1 + x) -2 + 10x = (1 * 3x + x * 3x) -2 + 10x = (3x + 3x2) Solving -2 + 10x = 3x + 3x2 Solving for variable 'x'. Combine like terms: 10x + -3x = 7x -2 + 7x + -3x2 = 3x + 3x2 + -3x + -3x2 Reorder the terms: -2 + 7x + -3x2 = 3x + -3x + 3x2 + -3x2 Combine like terms: 3x + -3x = 0 -2 + 7x + -3x2 = 0 + 3x2 + -3x2 -2 + 7x + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -2 + 7x + -3x2 = 0 Factor a trinomial. (-2 + x)(1 + -3x) = 0Subproblem 1
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Subproblem 2
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Solution
x = {2, 0.3333333333}
| 8x-2=-7+7x | | 2x+8=-5 | | -107=3-10x | | 7n+3=-67 | | 7=6-v | | 5c-3-4c=2c+2 | | 160+(16x+32)=180 | | 3a=1 | | (3x-4)(x^2-5x+1)= | | -9x^2+5x+12=0 | | 6(2a^2+3a)=18-12a | | 4x-18+4x=180 | | 15-(2m+4)=4+2m-13 | | -3y(6y+7)= | | 6x-20=4x+40 | | 7.34*1.8= | | 3+6x=-4y | | 7x^2-4x+.5717285714=0 | | -8r-4=7r-4 | | 8x^2+9x+6.5=0 | | x^2+3.81x+3.61=0 | | 2.5d=40+50 | | .2(d-6)=.3d+5-3+.1d | | x^2+2.40x+1.44=0 | | 4x+5=x+32 | | 57.86-9.95= | | 18k^3-48k^2+66k= | | 2.5d=0.4+50 | | -10x^3+5x^2+140= | | 300.000-24.677= | | 5+4d=-13-2d | | (2x+8)=(7x-1) |